Lincoln, Neb., Rev. Ordinances pt. 2, ch. 14, art. 26, § 8 (1895) - (:unkn) unknown (My University, 1895)
Prohibited discharging any cannon or artillery in any street, avenue, alley, park, or place within the limits of the city. Violators fined twenty-five dollars.
Keywords: DISCHARGE